Public administration research from a practitioner perspective - Streib, Gregory; Mark Rivera; Slotkin, Bert J. (2001)
Recent research has questioned both the rigor and theoretical development of public administration research. The proposed solutions have generally endorsed a more academically oriented research agenda. Authors have discussed practitioner needs, but the focus has been on the appropriateness of different research methods rather than the types of knowledge needed. We seek to contribute to this ongoing debate by comparing the knowledge needs identified by members of the International City/County Management Association (ICMA) with 15 years of research in Public Administration Review. We found much published research matching the neds of ICMA members, but it focused on a relatively narrow range of topics. We recommend incorporating a concern for relevance into efforts to improve public administration research. This will help to ensure that we build a knowledge base that makes a substantial contribution to practice. - Reproduced
Keywords: Public administration